2008
DOI: 10.1007/s11258-008-9411-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial division of labour of Schoenoplectus americanus

Abstract: If connected ramets are growing in heterogeneous environments, Division of Labour (DoL) among ramets potentially will result in more efficient sharing of resources and an overall benefit to the plants. As a result of DoL, connected ramets growing in a heterogeneous environment might achieve more biomass than ramets growing in a homogeneous environment. DoL has been demonstrated to occur in a few clonal plant species, although most studies simply focussed on biomass allocation, not on actual resource capturing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This has been experimentally shown for Trifolium repens [7,8], Fragaria chiloensis [5], [6], [11], [12], Potentilla anserina [13], and P. reptans [14], Glechoma hederacea [15], [16], G. longituba [17], [18] and Schoenoplectus americanus [19]. These studies clearly showed the high potential benefits of division of labour to enhance resource capture of clonal plants and thereby to increase their performance in heterogeneous habitats compared to non-clonal plants.…”
Section: Introductionmentioning
confidence: 61%
“…This has been experimentally shown for Trifolium repens [7,8], Fragaria chiloensis [5], [6], [11], [12], Potentilla anserina [13], and P. reptans [14], Glechoma hederacea [15], [16], G. longituba [17], [18] and Schoenoplectus americanus [19]. These studies clearly showed the high potential benefits of division of labour to enhance resource capture of clonal plants and thereby to increase their performance in heterogeneous habitats compared to non-clonal plants.…”
Section: Introductionmentioning
confidence: 61%
“…Physiological integration between vegetatively connected ramets often facilitates the colonization of environments where parts of the clone experience contrasting conditions. Coastal dunes, deserts, and wetlands are often dominated by clonal perennials, whose vegetative connections permit the ''homogenization'' of patchy resources and the amelioration of environmental stress (Alpert 1996;Pennings and Callaway 2000;Ikegami et al 2008). Translocation between ramets supported the encroachment of smooth brome into adjacent prairies; however, sharing of resources with the mother clone inhibited the proliferation of ramets invading a nutrient-poor prairie.…”
Section: Discussionmentioning
confidence: 99%
“…The success of clonal species is often attributed to their capacity to share resources among individual subunits. Translocation of resources, including water, carbohydrates, and minerals (Alpert and Mooney 1986;Lau and Young 1988;Tissue and Nobel 1988;Stuefer and Hutchings 1994;Alpert 1996;Wijesinghe and Hutchings 1997;Kemball and Marshall 1995), enables clonal species to exploit patchy resources (Alpert and Mooney 1986;Wijesinghe and Hutchings 1997;Ikegami et al 2008), ameliorate environmental stress (Amsberry et al 2000;Pennings and Callaway 2000), and reduce the impacts of competition and herbivory (Hartnett and Bazzaz 1985;Schmid et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a genotype might forage across the landscape and develop modules that differentially specialize in the uptake of resources (reviewed in Hutchings and de Kroon 1994). As Wang et al (2011) point out, this has been experimentally shown for Trifolium repens (Stuefer et al 1996), Fragaria chiloensis (Roiloa et al 2007), Potentilla anserina (van Kleunen and Stuefer 1999), Potentilla reptans (Stuefer et al 1994), Glechoma hederacea (Birch and Hutchings 1994), Glechoma longituba (Chu et al 2006), and Schoenoplectus americanus (Ikegami et al 2008). …”
Section: Spatial Heterogeneity Acclimationmentioning
confidence: 99%